Fabrication of carbon nanotubes/polypyrrole/carbon nanotubes/melamine foam for supercapacitor. Issue 2 (5th August 2013) - Liu, Feifei; Han, Gaoyi; Chang, Yunzhen; Fu, Dongying; Li, Yanping; Li, Miaoyu
ABSTRACT The carbon nanotubes (CNTs) have been loaded on the melamine foam (MF) to form the composite (CNTs/MF) by dip‐dry process, then polypyrrole (PPy) is coated on CNTs/MF (PPy/CNTs/MF) through chemical oxidation polymerization by using FeCl3·6H2O adsorbed on CNTs/MF as oxidant to polymerize the pyrrole vapor. Finally, CNTs are coated on the surface of PPy/CNTs/MF to increase the conductivity of the composite (CNTs/PPy/CNTs/MF) by dip‐dry process again. The composites have been characterized by X‐ray diffraction spectroscopy, scanning electron microscopy and electrochemical method. The results show that the structure of the composites has obvious influence on their capacitive properties. According to the galvanostatic charge/discharge test, the specific capacitance of CNTs/PPy/CNTs/MF is about 184 F g−1 based on the total mass of the composite and 262 F g−1 based on the mass of PPy (70.2 wt % in the composite) at the current density of 0.4 A g−1, which is higher than that of PPy/CNTs/MF (120 F g−1 based on the total mass of the composite and 167 F g−1 based on the mass of the PPy). Furthermore, the capacitor assembled by CNTs/PPy/CNTs/MF shows excellent cyclic stability. The capacitance of the cell assembled by CNTs/PPy/CNTs/MF retains 96.3% over 450 scan cycles at scan rate of 20 mV s−1, which is larger than that assembled by CNTs/PPy/MF (72.5%). © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39779.